2017
DOI: 10.1038/s41467-017-00780-5
|View full text |Cite
|
Sign up to set email alerts
|

SPA70 is a potent antagonist of human pregnane X receptor

Abstract: Many drugs bind to and activate human pregnane X receptor (hPXR) to upregulate drug-metabolizing enzymes, resulting in decreased drug efficacy and increased resistance. This suggests that hPXR antagonists have therapeutic value. Here we report that SPA70 is a potent and selective hPXR antagonist. SPA70 inhibits hPXR in human hepatocytes and humanized mouse models and enhances the chemosensitivity of cancer cells, consistent with the role of hPXR in drug resistance. Unexpectedly, SJB7, a close analog of SPA70, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(171 citation statements)
references
References 61 publications
4
153
0
Order By: Relevance
“…A). Treatment with SPA70 efficiently blocked RIF‐responsive induction of CYP3A4 as reported (Fig. B).…”
Section: Resultssupporting
confidence: 81%
“…A). Treatment with SPA70 efficiently blocked RIF‐responsive induction of CYP3A4 as reported (Fig. B).…”
Section: Resultssupporting
confidence: 81%
“…Ketoconazole Ketoconazole, L-sulforaphane, coumestrol, SPA70 (Cherian et al, 2018;Forman et al, 1998;Huang et al, 2007;Lemmen, Tozakidis, Bele, & Galla, 2013;Lin et al, 2017;Wang et al, 2008;Yeung, Sueyoshi, Negishi, & Chang, 2008) Biological (Aleksunes & Klaassen, 2012;Chen, Ferguson, Negishi, & Goldstein, 2003;Ferguson, Chen, LeCluyse, Negishi, & Goldstein, 2005;Ferguson, LeCluyse, Negishi, & Goldstein, 2002;Goodwin, Hodgson, D'Costa, Robertson, & Liddle, 2002;Maglich et al, 2004;Xu, Wang, & Staudinger, 2009;Yoshinari, Yoda, Toriyabe, & Yamazoe, 2010;Zhang, Huang, Chua, Wei, & Moore, 2002) UGTs Ugt1a1, Ugt1a9, Ugt2b34, Ugt2b35, Ugt2b36 UGT1A1 Ugt1a1, Ugt1a5, Ugt1a9 UGT1A1, UGT1A6, UGT1A3, UGT1A4 (Aleksunes & Klaassen, 2012;Maglich et al, 2004;…”
Section: Cinpa-1 Meclizinementioning
confidence: 99%
“…6), where BEL maintains its typical nature of interaction. Additionally, recent studies (Lin et al, 2017) have shown that the ligand interaction with residues of helix a12, a shared region between the LBP and the AF2 region (Supplemental Fig. 5; residues 420-429), is found to be critical for determining the agonist/antagonist activity of a compound.…”
Section: Belinostat Antagonizes Hpxr Target Gene Expressionmentioning
confidence: 98%
“…For example, sulforaphane antagonizes hPXR in vitro, but the concentrations needed to sustain this effect were not achieved in vivo, resulting in lack of an hPXR antagonistic effect in in vivo (Poulton et al, 2013). Recently, a novel hPXR antagonist has been discovered (Lin et al, 2017). However, the pharmacokinetics and safety profile of this compound in humans is unknown.…”
Section: Belinostat Antagonizes Hpxr Target Gene Expressionmentioning
confidence: 99%